2003
DOI: 10.1001/archpsyc.60.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Serious Mental Illness in the General Population

Abstract: The brevity and accuracy of the K6 and K10 scales make them attractive screens for SMI. Routine inclusion of either scale in clinical studies would create an important, and heretofore missing, crosswalk between community and clinical epidemiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
3,831
6
27

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 4,582 publications
(3,909 citation statements)
references
References 14 publications
45
3,831
6
27
Order By: Relevance
“…Scores were classified into low (scores of 6–11), moderate (scores of 12–19) or high (scores of 20–30) psychological distress 26. The K6 is effective at screening for serious mental disorders 27, 28, 29 and had excellent reliability in the current study (α = 0.81). Finally, the Short Form general health status question (SF11 30), which is an accurate predictor of future health care use, mortality and morbidity 30, was employed as a general indicator of physical and mental health.…”
Section: Methodsmentioning
confidence: 53%
See 1 more Smart Citation
“…Scores were classified into low (scores of 6–11), moderate (scores of 12–19) or high (scores of 20–30) psychological distress 26. The K6 is effective at screening for serious mental disorders 27, 28, 29 and had excellent reliability in the current study (α = 0.81). Finally, the Short Form general health status question (SF11 30), which is an accurate predictor of future health care use, mortality and morbidity 30, was employed as a general indicator of physical and mental health.…”
Section: Methodsmentioning
confidence: 53%
“…The American Association of Public Opinion Research (AAPOR) response rate 3 29 was 19.5% (21.7% landline; 17.8% mobile), the cooperation rate was 43.1% (38.0% landline; 49.7% mobile) and the refusal rate was 33.0% (42.0% landline; 24.4% mobile). An extended call cycle was employed for the landline frame, while a truncated call cycle, in which no more than four unanswered calls were made per week, was employed for the mobile frame.…”
Section: Methodsmentioning
confidence: 99%
“…This category was further dichotomized as high/middle (responses in the range 1–4) and low (responses in the range 5–6) [30,38]. Psychological distress was assessed using the six-item Kessler scale [39]. Each question (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The Cronbach α was .879, meaning that the scale showed good internal consistency. Following previous research, the summed score was dichotomized into two categories, indicating low (0–12 points) and high (>13) psychological distress [39]. …”
Section: Methodsmentioning
confidence: 99%
“…2.4.1 Mental health-General mental health was measured using a validated scale (Kessler et al, 2003) composed of the following six self-reported symptoms: feeling nervous, feeling hopeless, feeling restless or fidgety, feeling so sad or depressed that nothing could cheer you up, feeling everything was an effort, and feeling no good or worthless. Respondents were asked to rate the severity (0-4) of these symptoms during the one month of the past year when they were at their worst emotionally.…”
Section: Study Variablesmentioning
confidence: 99%